Tetraindole-based saddle-shaped organic dyes for efficient dye-sensitized solar cells. (October 2015) - Qian, Xing; Gao, Huan-Huan; Zhu, Yi-Zhou; Pan, Bin; Zheng, Jian-Yu
Abstract: Two new metal-free organic dyes which consist of a saddle-shaped tetraindole donor, a cyanoacrylic acid acceptor/anchoring group and a thiophene or bithiophene π-bridge have been successfully designed and synthesized for dye-sensitized solar cells. The two dyes showed good photoelectric properties, and the saddle-shaped structure of the tetraindole unit was found to be favorable for preventing intermolecular aggregation and enhancing the photovoltage. The two tetraindole-based dyes exhibited good photovoltaic performances in solar cells. An efficiency up to 6.46% with a high open-circuit photovoltage of 762 mV was achieved for the dyeJY15 with a 2, 2′-bithiophene moiety as the π-bridge using an iodine electrolyte under standard conditions. Graphical abstract: Highlights: Tetraindole-based organic dyes have been synthesized for the first time. The saddle-shaped structure is favourable for suppressing the dye aggregation. The dye with a bithiophene as the π-bridge exhibited better performances. An efficiency up to 6.46% has been achieved with a high V oc of 762 mV.